Types of exercise and training duration on depressive symptoms among older adults in long-term care facilities - Chen, Po-Jung; Chen, Kuei-Min; Hsu, Hui-Fen; Belcastro, Frank (Ageing research reviews, 2022)
Depression is associated with a greater risk of disability, cognitive impairment, and suicide. Older adults in long-term care facilities (LTCFs) are more likely to develop depression due to changes in family roles and separation from family members. The aim of this study was to synthesize and analyze the effects of different types of exercise and training duration on depressive symptoms of older adults in LTCFs. Relevant peer-reviewed journal articles published in English were identified through a search of six electronic databases up to June 2021. A total of 25 studies were included in the systematic review and 22 in the meta-analysis. The results of meta-analysis showed that exercise interventions reduced depression in cognitively intact older adults and in cognitively impaired older adults. Both exercising less than 150 min per week or more than 150 min per week, reduced depressive symptoms of older adults. In terms of exercise types, mind-body exercises, exergames, and strength training reduced depressive symptoms. Exercise has a positive effect on reducing depressive symptoms with mind-body exercises, exergames, and strength training producing the best effect. Regardless of cognitive impairment, older adults in LTCFs benefited from exercise in reducing depressive symptoms. •Older adults living in long-term care facilities often suffer from depression.•Exercise has positive effects on reducing depressive symptoms in older adults.•Regardless of cognitive impairment, depression could be improved through exercise.•Mind-body exercises, exergames, and strength training produced the best effect.